Identification of potent chromone embedded [1,2,3]-triazoles as novel anti-tubercular agents - Nalla, Viswanadh; Shaikh, Aslam; Bapat, Sanket; Vyas, Renu; Karthikeyan, M.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, M. (Royal Society Open Science, 2018)
A series of 20 novel chromone embedded [1,2,3]-triazoles derivatives were synthesized via an easy and convenient synthetic procedure starting from 2-hydroxy acetophenone. The in vitro anti-mycobacterial evaluation studies carried out in this work reveal that seven compounds exhibit significant inhibition against Mycobacterium tuberculosis H37Rv strain with MIC in the range of 1.56-12.5 mu g ml(-1). Noticeably, compound 6s was the most potent compound in vitro with a MIC value of 1.56 mu g ml(-1). Molecular docking and chemoinformatics studies revealed that compound 6s displayed drug-like properties against the enoyl-acyl carrier protein reductase of M. tuberculosis further establishing its potential as a potent inhibitor.

Iron catalyzed tandem ring opening/1,6-conjugate addition of cyclopropanols with p-quinone methides: new access to gamma,gamma-diaryl ketones - Shirsath, Sachin R.; Chandgude, Sagar M.; Muthukrishnan, M. (Chemical Communications, 2021)
An iron(iii) catalyzed tandem ring opening/1,6-conjugate addition of cyclopropanols to p-quinone methides leading to gamma,gamma-diaryl ketones has been described. This catalytic protocol provides a novel and efficient method to access gamma,gamma-diaryl ketone derivatives in good to excellent yields with high functional group tolerance. Importantly, gamma,gamma-diaryl ketone can be further functionalized to give a versatile set of useful products.

Iron mediated oxidative ring opening-homocoupling of cyclopropanols: facile access to 1,6-diketones - Shinde, Ravi A.; Shirsath, Sachin; Muthukrishnan, M. (ChemistrySelect, 2025)
We have developed a new approach for the synthesis of 1,6-diketones via iron-catalyzed ring opening of cyclopropanol with a nontoxic, inexpensive iron catalyst under open-air conditions. This method eliminates the need for additives and employs tert-butanol as an eco-friendly solvent. This methodology allows rapid access to a variety of symmetrical 1,6-diketones under mild conditions. Preliminary mechanistic studies revealed the involvement of radical pathways.
Keywords: 1; 6-Diketone synthesis; C & horbar; C bond cleavage; cyclopropanols; Homocoupling; Iron mediated